ANALISIS RHODAMIN B PADA SAUS TOMAT YANG BEREDAR DI SAMARINDA MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Diah Kusumaningsih; Alimuddin Alimuddin; Erwin Akkas (JURNAL KIMIA MULAWARMAN, 2020)
Abstract Analysis of rhodamine B in tomato sauce which is distributed in Samarinda city have been done. The identification are used chromatography paper and spectrophotometer UV-Vis in wavelength of 553nm. The result of research are showed in 5 of 20 samples that identified are positive of rhodamin B, which is tomato sauce in spring rools are 2.865 mg/L, tomato sauce in sausage are 2.033 mg/L, tomato sauce in meatball snacks are 2.008 mg/L, tomato sauce in cireng snacks are 1.058 mg/L, and the tomato sauce in tofu snacks 1.756 mg/L. Keywords: Rhodamine B, Chromatography Paper, Spectrophotometer UV-Vis